Adjusted dose regimens in dupilumab treatment for atopic dermatitis: Daily practice experiences - Jill I. Olydam; Linde E. M. deWijs; Tamar E. C. Nijsten; Joost vanRosmalen; Dirk Jan Hijnen (Wiley, 2022)
Abstract Background Clinical trials with dupilumab in atopic dermatitis (AD) patients showed a trend towards better effectiveness with a weekly or biweekly dosing interval, compared with extended dosing intervals. However, literature about adjusted dose regimens in daily practice is lacking. Objectives To evaluate adjusted dosing intervals of dupilumab for AD in daily practice. Methods An observational, longitudinal cohort study was conducted in AD patients who started dupilumab treatment in daily practice. Dosing intervals were adjusted upon shared decision making between physicians and patients in daily practice, without strict criteria. Disease courses of patients with shortened or extended dosing intervals were illustrated using spaghetti plots. In addition, data of patients who were treated with standard or extended dosing intervals were analysed using linear mixed effect (LME) models to determine the estimated effectiveness of extended dosing regimens. Results In total, 180 AD consecutive patients treated with dupilumab in daily practice were included in our study. Patients with an extended dosing interval (n = 28) had relatively low Eczema Area and Severity Index (EASI) scores at the time of interval adjustment (range: 0−7) and the majority of patients showed continuous effectiveness after adjustment. In patients with a shortened dosing interval (n = 26), the scores at the time of adjustment were more widespread (range: 0−34) and follow‐up showed variable disease courses. Based on the LME model, we found an overall continuous improvement of EASI scores in time, in patients with a regular and extended interval. Conclusions Patients with extended dosing intervals showed sustained effectiveness, similar to patients with standard dosing intervals. The effects of shortened intervals on disease severity could not be adequately analysed due to methodological limitations in this retrospective study.